Stress as a factor contributing to obesity in patients qualified for bariatric surgery – studies in a selected group of patients (a pilot study) - Boniecka, Iwona (Wideochir Inne Tech Maloinwazyjne, 2017)
INTRODUCTION: Recently, the incidence of obesity, especially extreme obesity, has significantly increased. It is connected with inappropriate lifestyle, including a high calorie diet, psychological and genetic factors, some medications, diseases or infectious factors. Nowadays, the consumption of food is not only to satisfy a physiological need, but also fulfils psychological needs. The most effective method of morbid obesity treatment is metabolic surgery. Moreover, food is considered to be a reward and method of coping with stress. In order to improve the efficiency of the surgical treatment, it seems significant to assess the effects of psychological factors on eating behaviours. AIM: To evaluate the effects of stress on eating habits that increase the risk of extreme obesity. MATERIAL AND METHODS: The study included 50 subjects qualified for bariatric surgery. The authors’ own questionnaire and standardised PSS-10 questionnaire by Cohen, Kamarcki and Mermelstein adapted by Juczyński and Ogińska-Bulik were used. RESULTS: These questionnaires indicated that patients felt a moderate levels of stress but with a tendency for high levels. The majority of respondents declared an increased appetite due to stress-causing factors. Reasons for snacking most frequently included negative emotions and feeling like eating something. Consumption of additional snacks was a way of coping with stress. Most frequently the subjects ate sweets and salty snacks, but also sandwiches, nuts, fruit and alcohol beverages. CONCLUSIONS: Psychological support may help morbidly obese people both to change nutritional habits and to cope with stress.